The Role of Islamic Religious Education Teachers in Overcoming Bullying Among Students in MIN 5 Boyolali - Nur Is Haryani; Meti Fatimah (South Sulawesi Education Development (SSED), 2024)
The aim of this research is to explore more deeply the role of Islamic religious education teachers in dealing with bullying among students at MIN 5 Boyolali. This research is qualitative research. The subjects of this research are Islamic religious education teachers. Meanwhile, the informants in this research were school principals, Islamic religious education teachers, student affairs officers and students. Data collection was obtained through observation, interviews and documentation. Meanwhile, data analysis uses data reduction, data presentation and data verification. The results show that the role of Islamic religious education teachers is to socialize bullying among school members, the school collaborates with parents and the school implements social regulations between students. Then the PAI teacher's strategy for dealing with bullying is by instilling Islamic Moral Values and Ethics, providing counseling guidance and building social skills.